Study on consumers' preferences and habits for over-the-counter analgesics use - Lefterova, A; Getov, I (Central European journal of public health, 2004)
The aim of the present study was to investigate consumers' knowledge, preference habits and use of the over-the-counter (OTC) analgesics. Our survey indicates the preferences of respondents in consultation with medical specialists (medical doctors and pharmacists) and their sources of information about drugs. A questionnaire survey was conducted during the periods March/April and July/August 2002 in 11 community pharmacies situated in Sofia (capital) and two towns in different regions in Eastern Bulgaria. From 250 questionnaires 222 were filled in correctly and analyzed (response rate 89%). Metamizole (dipyrone) is the most popular OTC analgesic--35% of the questioned patients prefer it to relieve the pain. In the second place is paracetamole (acetaminophen), but patients prefer to use it mainly for symptomatic treatment of cold/flu and influenza-like symptoms. More than 50% of patients have indicated that medical doctor recommended them the chosen OTC analgesic and in case of health problems during the therapy they prefer to consult him. They had more confidence in medical doctors' than pharmacists' recommendations and consultation. The main conclusion is that the pharmacists do not have the main say in the choice of OTC analgesics and their rational and correct use.
Keywords: Consumer Behavior; dospělí; Bulharsko; průzkumy a dotazníky; Female; Age Factors; Self Medication; Adult; Analgesics; ženské pohlaví; Surveys and Questionnaires; léky bez předpisu; věkové faktory; lidé; Nonprescription Drugs; Professional-Patient Relations; Humans; samoléčba; Middle Aged; Sex Factors; zdravé chování; Male; Bulgaria; chování spotřebitelů; sexuální faktory; Pharmacies; Health Knowledge, Attitudes, Practice; analgetika; zdraví - znalosti, postoje, praxe; lidé středního věku; lékárny; mužské pohlaví; vztahy mezi zdravotnickým pracovníkem a pacientem; Health Behavior